Índice de vulnerabilidade a inundações fluviais na Região do Baixo - Açu - Lima, Bárbara Almeida de (2021)
Natural disasters caused by river floods are among the most devastating natural hazards and cost many lives each year. This type of disaster represents a risk to the population and the economy since the impacts caused by floods are diverse, from loss of life to changes in the ecological cycle, as well as loss of structures. To prevent and mitigate this type of disaster, assisting in the planning of actions, it is important to know the vulnerability of the regions to this type of event. Normally, vulnerability is obtained from socioeconomic indicators, and studies that consider the impact of the flood on infrastructure are rare. Thus, this study aims to assess the vulnerability to river flooding considering, in addition to socioeconomic indicators, indicators that consider the effects of the shutdown of public services and the possibility of damage to existing buildings, using the cluster analysis to define the weights of the indicators . The study was carried out in the Baixo Açu region in Rio Grande do Norte and the. the results showed us that the cluster analysis presents itself as an adequate methodology for hierarchizing the indicators and that the studied region presents high fragility to flood events, indicating that a large part of the infrastructures surveyed are subject to being flooded, both the structures of support floods such as structures with potential pollution.